The 2021 Conference on Artificial Life 2021
DOI: 10.1162/isal_a_00376
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Multiple Fast Targets With Swarms: Interplay Between Social Interaction and Agent Memory

Abstract: The task of searching for and tracking of multiple targets is a challenging one. However, most works in this area do not consider evasive targets that move faster than the agents comprising the multi-robot system. This is due to the assumption that the movement patterns of such targets, combined with their excessive speed, would make the task nearly impossible to accomplish. In this work, we show that this is not the case and we propose a decentralized search and tracking strategy in which the level of explora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…This allowed for an individual agent's contribution, and hence the system's overall exploration and exploitation dynamic to be quantified. Kwa et al (2021a) and Kwa et al (2021b) later identified that a metric based on an agent's position relative to a target was unable to function when used in a scenario where multiple targets are to be tracked, such as situations defined under the Cooperative Multi-Robot Observation of Multiple Moving Targets (CMOMMT) framework. This led to the introduction of an engagement ratio, thereby allowing quantification of a swarm's EED in the presence of multiple targets by finding the proportion of agents actively moving towards a target.…”
Section: Sardinha Et Al (2020a)mentioning
confidence: 99%
See 4 more Smart Citations
“…This allowed for an individual agent's contribution, and hence the system's overall exploration and exploitation dynamic to be quantified. Kwa et al (2021a) and Kwa et al (2021b) later identified that a metric based on an agent's position relative to a target was unable to function when used in a scenario where multiple targets are to be tracked, such as situations defined under the Cooperative Multi-Robot Observation of Multiple Moving Targets (CMOMMT) framework. This led to the introduction of an engagement ratio, thereby allowing quantification of a swarm's EED in the presence of multiple targets by finding the proportion of agents actively moving towards a target.…”
Section: Sardinha Et Al (2020a)mentioning
confidence: 99%
“…To track a fast moving target Kwa et al (2020a), Kwa et al (2020b), Kwa et al (2021a) and Kwa et al (2021b), initially used inter-agent repulsion to promote area exploration. When a target was detected, an agent and its neighbors would activate a PSObased tracking behavior, allowing the target's information to be exploited, facilitating target tracking.…”
Section: Dedicated Exploration and Exploitation Strategiesmentioning
confidence: 99%
See 3 more Smart Citations